2019
DOI: 10.1111/trf.15183
|View full text |Cite|
|
Sign up to set email alerts
|

Cryopreserved platelets augment the inflammatory response: role of phosphatidylserine‐ and P‐selectin–mediated platelet phagocytosis in macrophages

Abstract: BACKGROUND Cryopreservation in dimethyl sulfoxide and storage at −80 °C extends the shelf life of platelets to at least 2 years, allowing greater availability in rural and military areas. While cryopreserved platelets (CPPs) have been extensively characterized for coagulation and thrombin generation, reports on the mechanism of adverse reactions to CPPs transfusion are scarce. Here, we tested the hypothesis that CPPs facilitate phagocytosis by Kupffer cells and subsequently promote the inflammatory response in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Cold storage (4 • C) of platelets may cause GPIbα receptor clustering and deglycosylation of N-glycans, a phenomenon that leads β-N-acetylglucosamine (β-GlcNAc) exposure and accelerated clearance from circulation [31][32][33]. These characteristic changes to GPIbα hydrocarbon sidechains are however not necessarily applicable to cryopreserved platelets because Waters et al could not find significant GPIbα clustering and Zhao et al found no increased exposure of β-GlcNAc after cryopreservation [28,34].…”
Section: Surface Receptor Expressionmentioning
confidence: 99%
“…Cold storage (4 • C) of platelets may cause GPIbα receptor clustering and deglycosylation of N-glycans, a phenomenon that leads β-N-acetylglucosamine (β-GlcNAc) exposure and accelerated clearance from circulation [31][32][33]. These characteristic changes to GPIbα hydrocarbon sidechains are however not necessarily applicable to cryopreserved platelets because Waters et al could not find significant GPIbα clustering and Zhao et al found no increased exposure of β-GlcNAc after cryopreservation [28,34].…”
Section: Surface Receptor Expressionmentioning
confidence: 99%
“…The initial response of platelets to tissue damage is the initiation of haemostasis via adhesion to sub‐endothelial structures and subsequent activation of the coagulation cascade; however, they also play a key role in recruitment and activation of leucocytes in order to contain and eliminate any potential infiltrating pathogens [3]. Attachment to leucocytes requires platelet activation and degranulation, which can be induced by stimulatory signals, including haemostatic agonists (thrombin, collagen and calcium), PAMPs/DAMPs or ex vivo storage [4,8,15,39,40]. Specifically, platelet activation results in α‐granule release, and the consequent localization of P‐selectin, CD40L and phosphatidylserine on the platelet surface, which facilitates leucocyte attachment (Figure 1 & Table 1) [3,41].…”
Section: The Role Of Platelets In Mediating Leucocyte Functionmentioning
confidence: 99%
“…1) [3,30] or through fibrinogen bound to platelet GPIIb/IIIa [42]. Activated platelets also exhibit externalized phosphatidylserine on the surface membrane, which has been shown to facilitate platelet attachment to macrophages and neutrophils through a range of potential surface receptors [39,43]. Notably, the formation of platelet–leucocyte aggregates results in the activation and degranulation of both cell types, increasing the local haemostatic and inflammatory effects [3].…”
Section: The Role Of Platelets In Mediating Leucocyte Functionmentioning
confidence: 99%
See 2 more Smart Citations